Post or Perish: SPA’s Presence on Social Media - Matias, Bernardo; Valente, Francisco; Leite, Diana; Paulo, Liliana; Lima, Fátima (Journal of the Portuguese Society of Anesthesiology, 2025)
Perspective Article - Not applicable